Role of radiologists in the diagnosis and management of adrenal disorders - Sota Oguro; Hiromitsu Tannai; Hideki Ota; Kazumasa Seiji; Hiroki Kamada; Yoshitaka Toyama; Kei Omata; Yuta Tezuka; Yoshikiyo Ono; Fumitoshi Satoh; Sadayoshi Ito; Tetsuhiro Tanaka; et al. (Endocrine Journal)
This study aimed to focus on the role of radiologists in the diagnosis and management of adrenal lesions, particularly primary aldosteronism (PA) and secondary hypertension. As hypertension affects more than one-third of the population in Japan, identifying secondary causes such as PA and adrenal lesions is crucial. Establishing a radiological differential diagnosis of adrenal lesions using advanced imaging techniques, such as computed tomography and magnetic resonance imaging, is crucial. Knowledge of the imaging findings of various benign and malignant adrenal lesions, such as adrenocortical adenomas, cortisol-producing lesions, pheochromocytomas, adrenocortical carcinoma, malignant lymphoma, and metastatic tumors, is necessary. Adrenal venous sampling (AVS) plays a crucial role in accurately localizing aldosterone hypersecretion in PA, especially when imaging fails to provide a clear diagnosis. This paper details the technical aspects of AVS, emphasizing catheterization techniques, anatomical considerations, and the importance of preprocedural imaging for successful sampling. Furthermore, we explore segmental adrenal venous sampling (SAVS), a more refined technique that samples specific adrenal tributary veins, offering enhanced diagnostic accuracy, particularly for microadenomas or challenging cases that may be missed with conventional AVS. The methodology for performing SAVS, along with the interpretation criteria for successful sampling and lateralization, is also outlined. Furthermore, radiologists have initiated treatments for unilateral PA, such as radiofrequency ablation, and play an integral role in the management of adrenal lesions. Collaborative approaches across clinical departments are required to enhance patient management in medical care involving the adrenal gland.